Complicated supravesical obstruction in patients with urolithiasis: multifactorial analysis of risk factors - M. M. Khasanov; U. A. Abdufattaev; A. A. Nomanov; Sh. T. Mukhtarov (Вестник урологии)
Introduction. Urolithiasis (UL) is a common disease observed in a huge number of people around the world. Supravesical obstruction (SVO) is a less frequent but potentially dangerous phenomenon that occurs when the urinary tract is blocked above the bladder, often resulting in impaired urinary passage and requiring surgery in most cases.Objective. To determine the risk factors of complicated supravesical obstruction in patients with urolithiasis.Materials & methods. We have conducted a retrospective study of diagnostic and treatment results of patients with SVO suffering from UL. Inclusion criteria: patients with established UL and SVO. Exclusion criteria: cancer and/or specific infection leading to SVO. From 2017 to 2019, 6250 patients with SVO were screened and treated at our centre. After assessing compliance with the inclusion and exclusion criteria, 1106 patients were selected for the study. We studied the risk factors leading to complicated course of SVO.Results. We evaluated the risk factors for the development of complicated SVO in patients with UL. All results are presented by EXP(B), with a 95% confidence interval in square brackets: complex kidney stones — 5,326 [2,247 – 9,296], ureteral stones — 12,251 [7,256 – 21,226], double-sided stones — 7,256 [2,158 – 9,255], disease length — 4,324 [1,782 – 8,256], urinary tract infection — 19,258 [4,258 – 26,248], blood leukocytosis — 15,116 [3,985 – 21,256], high serum creatinine — 10,244 [5,269 – 16,254], high serum glucose — 5,226 [3,145 – 11,254].Conclusion. The results of the study suggest that blocking renal and ureteral stones, double-side stones, upper urinary tract infection, low creatinine clearance, diabetes mellitus and disease length are significant risk factors for complicated course of SVO.